Creationism's Trojan horse the wedge of intelligent design - Forrest, Barbara, 1952-; Gross, Paul R. (Oxford : Oxford University Press, 2004)
The authors present a critical examination of 'intelligent design', a theory of biological diversity which is promoted by creationists as an alternative theory to evolution. Forrest & Gross contend that 'design theory' proponents have produced no creditable scientific evidence to support their ideas.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Creationism -- United States; Evolution (Biology) -- Religious aspects -- Christianity; Intelligent design (Teleology); Creationism -- Study and teaching -- United States; Evolution (Biology) -- Study and teaching -- United States; Intelligent design (Teleology) -- Study and teaching -- United States; Center for Science & Culture